LOW TEMPERATURE MUSHROOM (A. bisporus) DRYING WITH DESICCANT DEHUMIDIFIERS - Seyhan, FG; Evranuz, O. (Informa UK Limited, 2000)
ABSTRACT Cultivated mushrooms (Agaricus bisporus) slices of 2·5 and 5 mm thick were dried with dehumidified air at 20°, 30° and 40°C. Rehydration ability of dried mushrooms was used as criteria for the evaluation and determination of optimum conditions. Drying mechanism of the mushroom slices was expressed by unsteady state diffusion and the results were interpreted by Fickian model. Drying temperatures lower than 40°C promoted the production of light coloured mushrooms with high rehydration ratios. Diffusivity constants were in the range of 2·6−12×l0-11 m2/s and the activation energies varied in the range of 23·5−30·3 kJ/gmol depending on the temperature and sample thickness.